1999
DOI: 10.1080/00221329909595560
|View full text |Cite
|
Sign up to set email alerts
|

Genre of Music and Lyrical Content: Expectation Effects

Abstract: This study was designed to examine whether people's expectations differ regarding how music lyrics affect individual behavior as a function of music genre. Because legislative attention and media publicity have been biased against certain types of popular music (i.e., heavy metal and rap), the authors expected that those genres of music would be viewed more negatively than other genres of popular music, for which there has been little or no negative publicity (i.e., pop and country). Participants (N = 160 coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
0
22
0
7
Order By: Relevance
“…Musical samples were examined for sections that contained only a repetitive groove in order to avoid the influence of ratings via changes in rhythm, other auditory cues, or lyrics [4750]. Each section was parsed into a sixteen-measure (approximately 15 seconds) sample, containing no breaks or lyrics, but representative of the groove.…”
Section: Methodsmentioning
confidence: 99%
“…Musical samples were examined for sections that contained only a repetitive groove in order to avoid the influence of ratings via changes in rhythm, other auditory cues, or lyrics [4750]. Each section was parsed into a sixteen-measure (approximately 15 seconds) sample, containing no breaks or lyrics, but representative of the groove.…”
Section: Methodsmentioning
confidence: 99%
“…For example, as part of a study conducted to examine the effect of taste in music genre on the amount of time young people spent listening to music, Ramsay (1998) found that ''those whose favourite type of music was dance/ techno/trance, heavy metal/thrash, or rap/hip hop, spent the most time listening to recorded music'' (p. 11). Similarly, Ballard et al (1999) considered the impact of lyrics associated with specific genres upon young people's behaviour and found that those labelled as heavy metal or rap were perceived as less likely to inspire pro-social behaviour but not more likely to inspire antisocial behaviour than the same lyrics labelled as country or pop. These findings, however, do not afford the opportunity to build on or develop marketing strategies targeted at particular groups of youth consumers.…”
Section: Re-evaluating the Segmentation Of The Music Marketmentioning
confidence: 97%
“…Hansen and Hansen (1991b) found that, even without reading the musical lyrics, novice heavy metal listeners could extract themes of sex, suicide, violence, and the occult from songs. Ballard, Dodson, and Bazzini (1999) found that lyrics labeled as heavy metal or rap were less likely to inspire prosocial behavior than the same lyrics labeled as pop and country.…”
Section: Music and Attitudesmentioning
confidence: 97%